Acid Extraction And Characterization Of Pectin From Malaysian Honeydew (cucumis Melo L. Var. Inodorous) Peels As An Alternative For Halal Food Thickener - Siti Radhiah Omar; Nurul Afiqah Md Hamsan; Siti Nazirah Omar (Penerbit UTM Press, 2024)
Non-Indexed Publication